Pengaruh Pemberian Buah Kurma (Phoenix Dactylifera L) terhadap Peningkatan Kadar Hemoglobin dan Feritin pada Mahasiswi - Aisah Aisah; Rosfita Rasyid; Zelly Dia Rofinda; Masrul Masrul (Universitas Baiturrahim, 2022)
Young women are one of the groups that are vulnerable to nutritional deficiency problems. Nutrients in the blood can be recognized through hemoglobin levels. Foods that are high in iron and which aid in the absorption of iron can increase hemoglobin serum and ferritin levels. The purpose of this study was to determine the effect of giving ajwa dates (Phoenix Dactylifera L) on the increase in hemoglobin levels of female adolescents at the Baiturrahim College of Health Sciences, Jambi. The research design was a quasi-experimental study on 44 young women who were selected by purposive sampling. Subjects were divided into 2 groups, control and treatment groups. The treatment group was given ajwa dates at a dose of 1.25 g / BW for 14 days. Data analysis used t-dependent test. Results of the The mean pretest Hb levels were 11.7 gr / dl (control) and 10.9 gr / dl (intervention), the mean ferritin serum levels were 41,2 μg / L (control) and 36.5 μg / L (intervention). The mean post-test Hb levels were 11.9 g / dl (control) and 12.3 g / dl (intervention), the mean ferritin serum levels were 46.4 μg / L (control) and 58.8 μg / L (intervention). The results of statistical tests showed that there was an effect of giving Ajwa dates on hemoglobin and ferritin serum levels of anemia in adolescent girls with p = <0.001. Based on the results of the research and discussion, it can be concluded that the distribution of ajwa dates for young women can increase hemoglobin and ferritin levels. It can be seen from the increase in the average hemoglobin level in the intervention group before treatment was 10.9 and after treatment was 12.3 and The mean ferritin level in the intervention group before treatment was 36.5 and after treatment was 58.8.